Regulation of the non-steroid anti-inflammatory drug «Diclofenac sodium» in the air environment of populated places - Nikolaieva, Ya.Yu. (Medicni Perspektivi, 2025)
The most common group of drugs today are non-steroidal anti-inflammatory drugs, among which diclofenac sodium is one of the most widely used. It has a pronounced anti-inflammatory, analgesic and moderate antipyretic effect by inhibiting the synthesis of prostaglandins. This active pharmaceutical ingredient belongs to the second class of the Biopharmaceutical classification system, which has a high degree of permeability through biological membranes, which leads to the possibility of absorption of diclofenac sodium already in the stomach, thereby causing unwanted side and negative effects. Considering the large volumes of production and possible serious side effects of this active pharmaceutical ingredient, it is advisable to control the level of this substance in atmospheric air. The purpose of this work was to scientifically substantiate the hygienic regulation of diclofenac sodium in the atmospheric air of populated areas based on studies of the toxicological properties of this active pharmaceutical ingredient. Experimental animals (102 non-linear white mice, 136 non-linear white rats of both sexes, 60 short-haired mice) were divided into experimental and control groups of 6 individuals each. Based on the obtained indicators of lethality of experimental animals, using the method of probit analysis, the indicators of toxicity during acute exposure of the substance were determined – semi-lethal dose with a single intragastric administration of DL50 for female rats (54.83 mg/kg), DL50 for mice (550 mg/kg), DL50 for rats-females (104.4 mg/kg), and CL50 for male rats (243.11 mg/m3), CL50 for mice (71.61 mg/m3). According to subchronic exposure, it was established that diclofenac sodium has supercumulative activity, since the cumulative coefficients for subacute administration to mice and rats are <1 (0.94 and 0.96, respectively). It was determined that this substance does not have a pronounced irritating effect on the mucous membrane of the eyes and does not exhibit allergenic properties. Does not cause sensitization of the body. It is shown that the possibility of developing acute poisoning from a single inhalation exposure to diclofenac sodium is unlikely, which is confirmed by the coefficient of the possibility of inhalation poisoning (СPIP=0.000032). In turn, the low value of the Limch indicator (1.18 mg/m3) indicates the real danger of developing chronic inhalation poisoning with diclofenac sodium. Zbiol is 60.7, which indicates a significant sign of the ability to accumulate in the body. Expressed cumulative properties of this substance increase the risk of chronic poisoning. The maximum one-time maximum permissible concentration (MPC) in the atmospheric air of populated areas at the level of 0.03 mg/m3 was determined and substantiated. Thus, it is expedient to control and monitor the air environment during the production of medicinal products in order to prevent diclofenac sodium from entering the sanitary protection zones.